Cardiac shock wave therapy-induced exosome derived from OGD/R-treated H9c2 cells carrying miR-98-5p promote HUVECs angiogenesis - Lizhou Wu; Zhan Li; Wenhui Song; Li Zhang; Kuan Li; Haiyan Wang (Scientific Reports)
Abstract Cardiac shock wave therapy (CSWT) as an effectual therapy can activate the function of exosomes to a certain extent. Here, we attempted to examine the role of CSWT in exosome released from ischemic cardiomyocytes and its function in myocardial ischemia recovery. The exosomes derived from OGD/R-treated H9c2 (H9c2-OGD/R-Exo) and CSWT-treated OGD/R-stimulated H9c2 (CSWT-H9c2-OGD/R-Exo) were performed with small RNA sequencing to determine miRNAs that differentially expressed. After miR-98-5p inhibitor transfection, H9c2 were subjected to OGD/R and co-cultured with CSWT-H9c2-OGD/R-Exo, the cell viability, LDH and cell apoptosis were assessed. The transfected HUVECs were co-cultured with CSWT-H9c2-OGD/R-Exo, then HUVECs viability, angiogenesis, migration and invasion were assessed. The luciferase reporter gene assay was conducted to prove the targeting relation between miR-98-5p and FOXN3. miR-98-5p was highly enriched in CSWT-H9c2-OGD/R-Exo in compared with H9c2-OGD/R-Exo. CSWT-H9c2-OGD/R-Exo could improve cell viability, inhibit LDH and cell apoptosis. And miR-98-5p released by CSWT-H9c2-OGD/R-Exo promoted HUVECs viability, angiogenesis, migration and invasion. Further FOXN3 was defined as the downstream target gene of miR-98-5p, and miR-98-5p overexpression decreased FOXN3 expression in HUVECs. Besides, the suppression effects of miR-98-5p inhibitor on HUVECs proliferation, angiogenesis and metastasis was partly blunted by FOXN3 silencing. miR-98-5p released from CSWT-H9c2-OGD/R-Exo promoted HUVECs proliferation, angiogenesis and metastasis through directly targeting and suppressing FOXN3 expression.